Microalbuminuria in Type 1 Diabetes Mellitus Children (Medical Forum Monthly, 2020)
Objective: The basal bolus regimen proved to be the most effective way of controlling glycemic index but unfortunately, its supply is limited in resource-limited and remote areas. Due to poor control of glycemic index, patients face Long-term complications such as renal parenchymal disease. It is therefore most important to do frequent screening of children suffering from type 1 diabetes irrespective of duration of their disease in order to justify care for type 1 diabetes sufferers.Study Design: Cross-Sectional StudyPlace and Duration of Study: This study was conducted at the Arif Memorial Teaching Hospital Lahore on March 2019 to February 2020.Materials and Methods: At endocrinology clinic, about 40 children suffering from type 1 diabetes mellitus underwent urine albumin creatinine ratio (UAC) after early morning urine submission over span of a 6-months. The resulted ratios obtained were compared between disease duration (< 5 years and > 5 years) and between insulin type regimen types 1 either mixtard or basal bolus. All the children who reported elevated UAC ratio were put on retesting of their levels after a period of 3 months.Results: About 25 females and 15 male members participated and the mean UAC ratio was calculated to be 125mg/g with a range of 6.00 − 899 mg/g. About fifteen candidates (10 diagnosed with span of less than five years) had value of UAC ratio ≥ 31mg/g alongwith a mean of 195.0. When the UAC ratio repeated for these candidates it came out to be 144.35 mg/g. All the children who were put on mixtard regimen and suffering from diabetes for greater than five years span had higher UAC ratio as compared to candidates who were taking basal bolus regime and had diabetes for less than five years of duration.Conclusion: Micro albuminuria showed higher prevalence in type 1 diabetes sufferers who were having this disease for span of greater than five years and were put on mixtard régime.